Analisis Kritis terhadap Relevansi Asas Ne Bis In Idem dalam Perkara Perceraian - Dharma Setiawan Negara; Erwin Susilo; Lufsiana (Jurnal Hukum Lex Generalis, 2025)
Marriage in Indonesia is regulated by Law Number 1 of 1974 concerning Marriage in conjunction with Law Number 16 of 2019. One form of dissolution of marriage is through divorce decided by the court. This study examines the application of the principle of ne bis in idem in divorce cases, namely the legal principle that prohibits the retrial of the same case that has obtained permanent legal force. This study found differences in academic opinion regarding its application in divorce cases. Some legal experts argue that ne bis in idem applies in divorce cases, while others consider this principle inappropriate to apply considering the dynamics of emotional relationships and the possibility of new legal facts emerging. This study also discusses the regulation of divorce law in Indonesia, both for Muslims and non-Muslims, divorce procedures, and the legal consequences that arise, such as child custody and division of joint property. The findings indicate the need for special regulations, for example through a Circular of the Supreme Court, to provide legal certainty in the application of the principle of ne bis in idem in divorce cases.